Analysis of the Influence of Accounting Information Disclosure on Investors’ Decision-Making in Corporate Social Responsibility Report - Bian, Wenjie (Transactions on Economics, Business and Management Research, 2023)
This paper discusses the influence of accounting information disclosure on investors’ decision-making and corporate social responsibility. First of all, accounting information disclosure provides investors with important data about the financial situation and operating performance of enterprises, helping them to evaluate investment risks and returns. Secondly, disclosure also reflects the fulfillment of corporate social responsibilities, including charitable donations, environmental protection, employee benefits, etc. Transparency, timeliness and information quality help to build investors’ trust and attract more investment. In addition, the disclosure of accounting information will help investors better understand the risks and opportunities of enterprises and help them formulate more sensible investment strategies.